Povezanost odnosa sila-hitrost med nalogama navpičnega skoka in sprinta pri odbojkarjih - Pleša, Jernej (Šport (Ljubljana), 2021)
The force-velocity (FV) profiling has recently been proposed as a tool to identify the neuromuscular capabilities of athletes and to optimized the training based on the obtained results. The FV relationship allows the identification of the mechanical capabilities of musculoskeletal system to produce force, power and velocity. In this study, we checked the correlations between the variables obtained from the FV relationship in a) countermovement jump and b) sprint, on a sample of volleyball players. Forty-four male volleyball players (age: 20.8 ± 4.0 years) performed countermovement jumps with incremental loads from bodyweight to 50-100 kg (depending on the individual capabilities). Participants also performed 25-meter sprint with split times being recorded for the purpose of FV relationship calculation. Pearson’s correlation coefficient showed that there were no statistically significant correlations (r = 0,008–0,18; p > 0,05) between FV variables in vertical jump and sprint. The absence of correlations suggests that each of the movement tasks provides insight into different, independent mechanical capabilities of the muscles. Both of the movement tasks present important components of volleyball game. Thus for the detailed assessment of mechanical capacity of the lower body muscles in volleyball players, the evaluation of both vertical jump and sprint FV relationship is recommended. Despite the indicated practical applications of the FV relationship in vertical jump and sprint, further research, studying the correlations between FV relationship and sport-specific performance is needed, to know more about the usefulness of FV relationship in volleyball training process.
Keywords: capacity; force-velocity profiling; mišice; muscles; navpični skok; odbojka; odnos sila-hitrost; sprint; vertical jump; volleyball; zmogljivost